The Difference in TBSA Estimation Between Emergency Room and Burn Unit in Second Tier Hospital in Central Jakarta - Wardhana, Aditya; Winarno, Gammaditya A.; Tanjunga, Sanjaya F.; Zidna, An’umillah Arini; Augiani, Amani S. (Lingkar Studi Bedah Plastik Foundation, 2021)
Introduction: Burn TBSA estimation is essential to administer fluid resuscitation. There are some methods, including Rule of 9 and Lund-Browder Chart. This study aims to identify the difference in TBSA estimation in Emergency Room & Burn Unit. Method: We conducted a retrospective cross-sectional study in design. The Inclusion criteria are patients admitted to the Jakarta Islamic Hospital Cempaka Putih (JIHCP) burn unit between April 2015-September 2018, acute patients who have complete demographic data, complete TBSA estimation in the emergency room (ER) and burn unit (BU). Exclusion criteria are patients who do not have complete demographical data and incomplete TBSA estimation between the emergency room and burn unit. The estimation of TBSA in the emergency room is done by General Practitioner, while in the burn unit is done by Plastic Surgeon. Result: Of all 160 patients admitted, 142 patients are eligible in the inclusion criteria. Most of it was adult males with an average of 28.3 years old, suffering a grade II burn injury caused by scald. There is a higher mean of TBSA estimation in the Emergency room with 15.83 (SD 12.21) compared to the Burn Unit with 12.92 (SD 12.00). The maximum TBSA overestimation in ER reaches 24% TBSA than BU, while the minimum is 0.5%. The Maximum TBSA underestimation in ER reaches 20% TBSA than BU, while the minimum underestimation is also 0.5%. On average, ER overestimates about 6.7% TBSA and underestimates about 2.8% TBSA compared to BU. Conclusion: The emergency room tends to overestimate the TBSA, with an almost 3% difference in mean (p<0.05). There is an occurrence of a maximum 24% TBSA overestimation while averaging 6.7% TBSA.